Migraine Pathophysiology and Treatment - J Gordon Millichap (Pediatric Neurology Briefs)
The proceedings of a symposium on “The scientific basis of migraine management” held Feb 1999 at Lake Louise, Alberta, Canada, are reported from the University of Calgary and other centers.